Friedrich Welwitsch and his contributions to the exploration and study of the flora of São Tomé and Príncipe, Gulf of Guinea, with typification of three names described from his collections - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2020)
Friedrich Welwitsch (1806–1872) is best known for his botanical work in Angola in south-tropical Africa. However, he also was one of the first plant collectors on the islands of São Tomé and Príncipe, Gulf of Guinea, while en route to Angola in 1853, and again seven years later when returning to Lisbon, Portugal. The contributions of Welwitsch to the floristics of these two islands are discussed. Reference is also made to the other mid-19th century botanical collectors who were active in São Tomé and Príncipe. The typification of the names Ehretia scrobiculata, Hernandia beninensis, and Leea tinctoria, which are all based on Welwitsch specimens, is clarified. Two endemics of the Gulf of Guinea islands have names coined by Welwitsch. Their nomenclature is clarified, and the names are here second-step lectotypified. We show that authorship of the name Leea tinctoria should be attributed to Welwitsch, not to ‘Lindley ex Baker’.